OPTIMALISASI PENGELOLAAN DATA PROGRAM KARTU HUMA BETANG SEJAHTERA DAN ADMINISTRASI KEUANGAN PADA BIRO PEMERINTAHAN PROVINSI KALIMANTAN TENGAH - Yulia Hana; Ferry Christian; Ricky Yunisar Setiawan (Jurnal Pengabdian Masyarakat Sabangka, 2026)
The implementation of effective administrative systems and structured government program data management is essential in supporting transparent and accountable governance. This study aims to describe the optimization of data management for the Kartu Huma Betang Sejahtera program and financial administration at the Bureau of Government, Central Kalimantan Provincial Government. The activity was conducted through the Merdeka Belajar Kampus Merdeka (MBKM) internship program using a Service Learning approach with descriptive qualitative methods. Data collection techniques included observation, interviews, and documentation. The results indicate that administrative support activities—including official travel data input, preparation of accountability and activity reports, document archiving, and management of strategic regional program data—contributed to improving administrative efficiency and data organization. The optimization of these processes supports more structured governance and enhances institutional effectiveness.